An Enhancement of Social Capital of fprm Urban Fabric. a Comparison of Three Cities in Indonesia - Barliana, Ms; Cahyani Permana Sari, Diah; Ardian Pancapana, Dodit; Paramita, Beta (International Journal of Engineering and Technology, 2018)
The city is a living entity, especially about any urban form; however, the quality of the city would refer to physical qualities. Urban design and spatial planning of the city are good on one hand, and the cultural essence fortified on the other hand. It is important to encourage the strengthening of social capital. Indeed, it is about quality of the city to accommodate quality of life of its citizens. The structure of the physical environment within the city is formed by structural elements (artificial) which cover all elements such as buildings, and various other technical infrastructures connected differently from each other.This study was carried in Surabaya and Bandung metropolitan city and Surakarta city in Indonesia. This study aims to give a description of urban form quality of each city; the perception of citizens of their own city, then gives the reciprocal of capital, social value, the sense toward urban form and space, which shown in their daily activity.The results show that Bandung and Surakarta have urban form quality in the â€œlowâ€ level, meanwhile Surabaya has the â€œhighâ€ level. Surabaya with â€œhighâ€ level physical quality has correlation with â€œhighâ€ level of their citizen perception. But somehow, in Bandung and Surakarta this physical quality level has different level perception of their citizen as the image of the city. The perception of Bandung City Image by 43 social communities has mentioned that Bandung has â€œhighâ€ level. This perception also shown in 40 social communities in Surakarta, that its city image has â€œhighâ€ level.Â Â